First, let's simplify the left part of the equation using the following properties:
![\begin{gathered} (a^b)/(a^c)=a^(b-c) \\ (a^b)^c=a^(b\cdot c) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/golbfpld1g4oe5vlpfd62kn7cre995amnv.png)
So we have:
![(\frac{13^0^{}}{13^3})^{(1)/(3)}=(13^(0-3))^{(1)/(3)}=(13^(-3))^{(1)/(3)}=13^{-3\cdot(1)/(3)}=13^(-1)](https://img.qammunity.org/2023/formulas/mathematics/college/3hu5ec8432u2vj4kb88wbpsg7g6s844fwo.png)
The statement is wrong because the exponent of the numerator is 0 and not 1, like the exponent on the second given equation (which is correct), so the result is different.